2014
DOI: 10.1152/ajpendo.00552.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of 25-hydroxycholesterol regulates lipid metabolism, inflammatory responses, and cell proliferation

Abstract: Ren S, Ning Y. Sulfation of 25-hydroxycholesterol regulates lipid metabolism, inflammatory responses, and cell proliferation. Am J Physiol Endocrinol Metab 306: E123-E130, 2014. First published December 3, 2013 doi:10.1152/ajpendo.00552.2013.-Intracellular lipid accumulation, inflammatory responses, and subsequent apoptosis are the major pathogenic events of metabolic disorders, including atherosclerosis and nonalcoholic fatty liver diseases. Recently, a novel regulatory oxysterol, 5-cholesten-3b, 25-diol 3-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 98 publications
4
45
0
Order By: Relevance
“…Additionally, the effects of the continuous presence of high concentrations of certain hydroxycholesterol sulfates, which have been proved to have regulatory capacities in some cases ( 26,28 ), should be studied in detail. position 24.…”
Section: Methods Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the effects of the continuous presence of high concentrations of certain hydroxycholesterol sulfates, which have been proved to have regulatory capacities in some cases ( 26,28 ), should be studied in detail. position 24.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Some of the most relevant monosulfated and disulfated hydroxysterols have been previously identifi ed, synthesized, and characterized (25)(26)(27)(28). Among these, 25-hydroxycholesterol-3-sulfate (25OHC3S) has been studied with more detail, and its physiological activities and regulatory capacities have been described ( 28 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CYP7B1 hydroxylates 25HC to form 7␣25HC, an oxysterol that also plays an important role as a guidance cue for B cells through interaction with Epstein-Barr virus induced receptor 2 (reviewed in Daugvilaite et al 2014). Recent work has also identified hydroxysterol sulfotransferase 2B1b as the enzyme that catalyzes sulfation of 25HC to 25-hydroxycholesterol-3-sulfate (25HC3S) (Ren and Ning 2014). Studies have generally found the sulfated oxysterol to have effects opposing to 25HC on both inflammation and metabolism (Ren and Ning 2014).…”
Section: Future Outlookmentioning
confidence: 99%
“…Recent work has also identified hydroxysterol sulfotransferase 2B1b as the enzyme that catalyzes sulfation of 25HC to 25-hydroxycholesterol-3-sulfate (25HC3S) (Ren and Ning 2014). Studies have generally found the sulfated oxysterol to have effects opposing to 25HC on both inflammation and metabolism (Ren and Ning 2014). While metabolomic profiling revealed no significant increase in sulfated oxysterol levels during IFN stimulation of macrophages (Blanc et al 2013), it remains to be seen if 25HC3S plays a role in the antiviral response in other cell types and tissues, such as the liver, where 25HC3S has been shown to be localized in the nuclei and mitochondria (Ren et al 2006).…”
Section: Future Outlookmentioning
confidence: 99%